Orotidine Monophosphate Decarboxylase – A Fascinating Workhorse Enzyme with Therapeutic Potential. Issue 5 (20th May 2015) - Fujihashi, Masahiro; Mnpotra, Jagjeet S.; Mishra, Ram Kumar; Pai, Emil F.; Kotra, Lakshmi P.
Abstract: Orotidine 5′-monophosphate decarboxylase (ODCase) is known as one of the most proficient enzymes. The enzyme catalyzes the last reaction step of the de novo pyrimidine biosynthesis, the conversion from orotidine 5′-monophosphate (OMP) to uridine 5′-monophosphate. The enzyme is found in all three domains of life, Bacteria, Eukarya and Archaea. Multiple sequence alignment of 750 putative ODCase sequences resulted in five distinct groups. While the universally conserved DxKxxDx motif is present in all the groups, depending on the groups, several characteristic motifs and residues can be identified. Over 200 crystal structures of ODCases have been determined so far. The structures, together with biochemical assays and computational studies, elucidated that ODCase utilized both transition state stabilization and substrate distortion to accelerate the decarboxylation of its natural substrate. Stabilization of the vinyl anion intermediate by a conserved lysine residue at the catalytic site is considered the largest contributing factor to catalysis, while bending of the carboxyl group from the plane of the aromatic pyrimidine ring of OMP accounts for substrate distortion. A number of crystal structures of ODCases complexed with potential drug candidate molecules have also been determined, including with 6-iodo-uridine, a potential antimalarial agent.